Plasticity of calcium signaling cascades in human embryonic stem cell-derived neural precursors - Forostyak, Oksana; Romanyuk, Nataliya; Verkhratsky, Alexei; Sykova, Eva; Dayanithi, Govindan (Stem cells and development, 2013)
Human embryonic stem cell-derived neural precursors (hESC NPs) are considered to be a promising tool for cell-based therapy in central nervous system injuries and neurodegenerative diseases. The Ca(2+) ion is an important intracellular messenger essential for the regulation of various cellular functions. We investigated the role and physiology of Ca(2+) signaling to characterize the functional properties of CCTL14 hESC NPs during long-term maintenance in culture (in vitro). We analyzed changes in cytoplasmic Ca(2+) concentration ([Ca(2+)]i) evoked by high K(+), adenosine-5'-triphosphate (ATP), glutamate, γ-aminobutyric acid (GABA), and caffeine in correlation with the expression of various neuronal markers in different passages (P6 through P10) during the course of hESC differentiation. We found that only differentiated NPs from P7 exhibited significant and specific [Ca(2+)]i responses to various stimuli. About 31% of neuronal-like P7 NPs exhibited spontaneous [Ca(2+)]i oscillations. Pharmacological and immunocytochemical assays revealed that P7 NPs express L- and P/Q-type Ca(2+) channels, P2X2, P2X3, P2X7, and P2Y purinoreceptors, glutamate receptors, and ryanodine (RyR1 and RyR3) receptors. The ATP- and glutamate-induced [Ca(2+)]i responses were concentration-dependent. Higher glutamate concentrations (over 100 μM) caused cell death. Responses to ATP were observed in the presence or in the absence of extracellular Ca(2+). These results emphasize the notion that with time in culture, these cells attain a transient period of operative Ca(2+) signaling that is predictive of their ability to act as stem elements.
Keywords: purinergní receptory; Cell Differentiation; Neural Stem Cells; Intracellular Space; Time Factors; vápník; Microscopy, Confocal; Calcium Signaling; Calcium Channels; glutamáty; Glutamates; Embryonic Stem Cells; počet buněk; konfokální mikroskopie; Receptors, Purinergic; embryonální kmenové buňky; Calcium; vápníková signalizace; Humans; biologické markery; nervové kmenové buňky; časové faktory; intracelulární prostor; vápníkové kanály; buněčná diferenciace; Biomarkers; Cell Count; lidé